Term structure dynamics and no-arbitrage under the Taylor Rule - Inhasz, Juliana (2009)
The term structure interest rate determination is one of the main subjects of the financial assets management. Considering the great importance of the financial assets for the economic policies conduction it is basic to understand structure is determined. The main purpose of this study is to estimate the term structure of Brazilian interest rates together with short term interest rate. The term structure will be modeled based on a model with an affine structure. The estimation was made considering the inclusion of three latent factors and two macroeconomic variables, through the Bayesian technique of the Monte Carlo Markov Chain (MCMC).